FOREIGN ECONOMIC RELATIONS OF AZERBAIJAN IN THE CONTEXT OF REGIONAL INTEGRATION - Artem Gennadevich Pylin (Проблемы постсоветского пространства, 2017)
The article are reviewed trade and investment relations in Azerbaijan for the period 2000-2014 years in the context of the problems of regional integration. Comprehensive analysis of foreign economic relations showed that Azerbaijan is trying to conduct a multi-vector and balanced foreign policy, taking into account the interests of the leading regional players (EU, Russia and Turkey), but without direct participation in integration projects. The most close trade and economic relations established between Azerbaijan, Georgia and Turkey, that indicates about formation of informal integration association as part of the trio.